2018
DOI: 10.1016/j.dcn.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The impact of atypical sensory processing on social impairments in autism spectrum disorder

Abstract: Altered sensory processing has been an important feature of the clinical descriptions of autism spectrum disorder (ASD). There is evidence that sensory dysregulation arises early in the progression of ASD and impacts social functioning. This paper reviews behavioral and neurobiological evidence that describes how sensory deficits across multiple modalities (vision, hearing, touch, olfaction, gustation, and multisensory integration) could impact social functions in ASD. Theoretical models of ASD and their impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
238
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(293 citation statements)
references
References 400 publications
17
238
0
13
Order By: Relevance
“…Studies in older children have shown similar associations between greater ASD symptomology and reduced resting-state fc between the visual network and other large-scale functional networks including motor and salience networks (74, 81). Given previous studies that have linked RRBs to atypical sensory response patterns including hyper responsivity to sensory stimuli and sensory seeking behavior (911, 14), our findings support the hypothesis that early disordered fc involving the visual network may engender later disruptions in higher order behaviors (82, 83). …”
Section: Discussionsupporting
confidence: 87%
“…Studies in older children have shown similar associations between greater ASD symptomology and reduced resting-state fc between the visual network and other large-scale functional networks including motor and salience networks (74, 81). Given previous studies that have linked RRBs to atypical sensory response patterns including hyper responsivity to sensory stimuli and sensory seeking behavior (911, 14), our findings support the hypothesis that early disordered fc involving the visual network may engender later disruptions in higher order behaviors (82, 83). …”
Section: Discussionsupporting
confidence: 87%
“…Exploring this matter further could yield insights as to developmental mechanisms underlying the emergence of ASD as well as provide new targets for screening and intervention. For example, several theoretical models posit that altered processing of sensory stimuli in infancy might contribute directly to the accumulation of later‐emerging social communication deficits in children with ASD (Thye, Bednarz, Herringshaw, Sartin, & Kana, ). Alternatively, it is plausible that our results reflect a more complex truth, wherein response patterns within and between children are characterized by high levels of variability and heterogeneity, reflecting the interplay of multiple aspects of development during a period of rapid maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in ASD are reported in all sensory domains (Thye, Bednarz, Herringshaw, Sartin, & Kana, 2018) and are linked to a disturbed underlying neural processing (Kern et al, 2007). For example, compared to typically developing children, children with ASD have a delay in the identification of speech syllables in lip-reading tasks and are less likely to integrate the audio-visual information obtained by the McGurk effect (Taylor, Isaac, & Milne, 2010).…”
Section: Introductionmentioning
confidence: 99%